Penguatan Basis Data Kemiskinan Melalui Aplikasi SIMNANGKIS di Kabupaten Kudus - Muhammad Helvanza; Suci Prasita Dewi (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2025)
This community service activity aims to strengthen the poverty database through the implementation of the SIMNANGKIS Application in validating poverty data in Kudus Regency, especially in Soco Village, Dawe District. The methods used in this activity include data collection, participatory observation, in-depth interviews, data verification of the Acceleration Map. Extreme Poverty Eradication (P3KE). The data verification process through SIMNANGKIS is carried out by integrating various aspects, such as data on the head of the family, asset ownership, income expenditure, housing conditions, stunting vulnerability, and geographic location. The results of this community service show that this application plays an important role in improving the accuracy and integrity of poverty data, thereby minimizing differences between BPS and P3KE data. The findings also revealed that field verification conducted through SIMNANGKIS helps identify ineligible households or vice versa, so that the distribution of social assistance can be more targeted. The implications of this activity are expected to be the basis for improving the data collection system and formulating more effective poverty alleviation policies.